The association between learning style, social demographic background, and pharmacology assessment result amongst first year medical students in Universiti Putra Malaysia during Covid-19 pandemic - Saat, Azmah; Mohd. Thani, Suryati; Salihan, Safuraa; Muhamad Saliluddin, Suhainizam (Universiti Putra Malaysia, 2022)
Introduction: A variety of medical treatments are based on the scientific understanding gathered from pharmacology studies. Thus, pharmacology is crucial in medicine. Many universities around the world have resorted to online learning of pharmacology as a result of the unique coronavirus epidemic, which has an indirect impact on the student’s academic achievement. Apart from learning styles, the socio-demographic background of a student, which includes the student’s family income, parental educational level, and residential area, is another important factor that influences pharmacology academic achievement. Methods: This is a cross-sectional study involving first-year medical students at the Faculty of Medicine and Health Sciences Universiti Putra Malaysia which used a questionnaire regarding the socio-demographic background and learning style. In addition, the pupils were given a set of pharmacological questions to assess their academic performance. Results: Findings revealed that the family income had a considerable impact on medical students’ academic performance with a significant value for the Chi-Square at p = 0.013. The pupils’ learning styles had no discernible impact on their academic success with an insignificant Fisher’s exact test value at p = 0.822. Conclusion: Lower-income students (those with parental income below the median) were significantly more likely to have poorer academic outcomes than their higher-income peers. Our findings imply that policymakers can prevent COVID-19 from worsening existing achievement gaps in higher education by focusing on resolving the economic and health burden imposed by COVID-19.